Characterization of an antibacterial dodecapeptide from pig as a potential food preservative and its antibacterial mechanism. Issue 5 (28th April 2020) - Lyu, Yinfeng; Yang, Chengyi; Chen, Tingting; Shang, Lu; Yang, Yang; Li, Jiawei; Shan, Anshan; Xiang, Wensheng; Cheng, Baojing; Zhang, Licong
Abstract : A membrane-active dodecapeptide was generated from porcine antimicrobial peptide with promising antimicrobial activity for application in the food industry as a potential bio-preservative to prevent microbial spoilage. Abstract : Antimicrobial peptides are believed to be promising bio-preservatives to prevent microbial spoilage through food processing and preservation. With the aim of developing short peptides with broad-spectrum antimicrobial activity and revealing their potential antimicrobial mechanism, a novel class of dodecapeptides were designed by introducing Trp into the hydrophilic face of RI12, a truncated α-helical peptide of porcine myeloid antimicrobial peptide-36 (PMAP-36). The antimicrobial activity study indicated that Trp endowed the peptides with higher antimicrobial potency, and the net charge of +5 was sufficient for the dodecapeptides to exert antimicrobial action. Taking hemolytic activity into consideration, the most promising peptide RI12[K3W] (RLWKIGKVLKWI-NH2 ) was screened with high antimicrobial activity and non-toxicity. The antimicrobial mechanism study revealed that RI12[K3W] possessed the ability to bind to LPS components and enhance membrane permeability, which was verified by membrane penetration assays. Flow cytometry and electron microscopy further confirmed that RI12[K3W] killed bacterial cells primarily by membrane damage. The results guide the potential application of antimicrobial peptides in the food industry as food preservatives to prevent bacterial contamination.